Soil biological properties and fungal diversity under conservation agriculture in Indo-Gangetic Plains of India - Choudhary, Madhu; Sharma, Parbodh Chander; Jat, Hanuman Sahay; McDonald, Andrew J.; Jat, Mangi Lal; Choudhary, Sharda; Garg, Neelam (Springer, 2018)
A field experiment was undertaken to evaluate the effect of conservation agriculture (CA) based management on soil biological properties, and on fungal diversity and abundance after 5 years of continuous cultivation. Treatments included four crop managements viz., conventional tillage (CT) rice-wheat (CT-RW; CT based), conventional tillage rice-zero tillage wheat and mungbean (CTR-ZTWMb; partially CA based), zero tillage rice-wheat-mungbean (ZT-RWMb; full CA based), and zero tillage maize-wheatmungbean (ZT-MWMb; full CA based). Full rice, maize, and mungbean crop residue and anchored wheat residue were recycled in CA-based managements, while CT-based management was without any residue. Full CA-based management (ZT-MWMb) recorded 43% higher organic carbon, 56% microbial biomass carbon, 70% microbial biomass nitrogen, 73% phosphatase activity, and 40% β-glucosidase activity, than CT-RW management. Ascomycota (55-74%) was the dominant phylum followed by Basidiomycota and Glomeromycota (0 to 3%); abundance of these phyla varied amongst managements. Ascomycota abundance was in order of CT-RW< CTR-ZTWMb< ZT-RWMb< ZT-MWMb, however, Basidiomycota and Glomeromycota did not follow any trend. Diversity indices such as species richness, evenness and Shannon-Wiener diversity index were in the order: ZT-MWMb> ZT-RWMb> CTR-ZTWMb> CT-RW. This study clearly showed that CA with all three proven principles (no-tillage, residue retention and crop diversification) in maize-wheat-mungbean system resulted in higher microbial activities, fungal diversity and species richness compared to other cereal based management systems.